2020
DOI: 10.3332/ecancer.2020.1055
|View full text |Cite
|
Sign up to set email alerts
|

A 10-year review of primary major salivary gland cancers

Abstract: Primary salivary gland cancers comprise a heterogeneous group of histological entities and represent less than 5% of head and neck malignancies. Surgical resection is the main treatment, and adjuvant radiotherapy is performed in selected cases. Chemotherapy is an option in metastatic or recurrent disease, with poor evidence. We aimed to review a 10-year experience of a cancer centre on major salivary gland cancers, focusing on clinical, pathological, treatment and patients' outcomes data. A total of 93 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
0
9
1
1
Order By: Relevance
“…Another study which also included children reported DFS of 63% which is lower than the DFS in the present study [23]. Furthermore, three studies which included adult patients with SGTs reported DFS of 54.6% [31] and 69% [32] which were lower than DFS observed in the present study but close to 71% which was reported in the study of Chen et al [4]. Although it has been shown that the survival of children and adolescent patients with SGTs is better than that of adults aged more than 50 years [33], still such relation is not very linear because some discrepancies have been reported.…”
Section: Discussioncontrasting
confidence: 76%
“…Another study which also included children reported DFS of 63% which is lower than the DFS in the present study [23]. Furthermore, three studies which included adult patients with SGTs reported DFS of 54.6% [31] and 69% [32] which were lower than DFS observed in the present study but close to 71% which was reported in the study of Chen et al [4]. Although it has been shown that the survival of children and adolescent patients with SGTs is better than that of adults aged more than 50 years [33], still such relation is not very linear because some discrepancies have been reported.…”
Section: Discussioncontrasting
confidence: 76%
“…SGCs can be classified into more than 20 subtypes, including mucoepidermoid carcinoma (MEC), adenoid cystic carcinoma (ACC), salivary duct carcinoma (SDC), acinic cell carcinoma (AciCC), and secretory carcinoma (SC) with widely variable clinical behavior. While each histiotype is individually rare, the group represents approximately 5% of head and neck cancers 3–5 . Surgery and radiation are the mainstays of local SGC therapy, but treatment options for inoperable, recurrent, and metastatic disease have been limited by poor response to cytotoxic chemotherapy 5 .…”
Section: Introductionmentioning
confidence: 99%
“…MSDC often presents in stage III-IV with lymph node metastasis, and its prognosis is notoriously poor. [9][10][11] Lymph node ratio (LNR), defined as the ratio of the number of metastatic lymph nodes to the number of resected lymph nodes, has been found to be an effective tool Abbreviations: AJCC, American Joint Committee on Cancer; AUC, corresponding area under curve; C-index, concordance index; DCA, decision curve analysis; ELN, examined lymph node; OS, overall survival; PORT, postoperative radiotherapy; LNN, lymph node number; LNR, lymph node ratio; MSDC, major salivary duct carcinoma; ROC, receiver operating characteristic; SDC, salivary duct carcinoma; SGCs, salivary gland cancers; SEER, surveillance, epidemiology, and end results.…”
Section: Introductionmentioning
confidence: 99%
“…MSDC often presents in stage III‐IV with lymph node metastasis, and its prognosis is notoriously poor 9–11 . Lymph node ratio (LNR), defined as the ratio of the number of metastatic lymph nodes to the number of resected lymph nodes, has been found to be an effective tool evaluating the prognosis of many types of tumors.…”
Section: Introductionmentioning
confidence: 99%